Analisis Faktor yang Memengaruhi Kebijakan Moneter Ekspor Subsektor Perikanan - Ramadhani, Fiska; Astuty, Sri; Kamaruddin, Citra Ayni; Rahim, Abd; Syafri, Muhammad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The export of Indonesia's fisheries subsector plays a crucial role in the national economy, but this sector faces challenges influenced by monetary policy, which can affect the competitiveness of fisheries products in international markets. This study aims to analyze the impact of monetary policy on the export of Indonesia’s fisheries products, focusing on factors such as the real exchange rate, interest rates, and inflation. A quantitative approach using time series methods is employed, utilizing secondary data from the Central Bureau of Statistics (BPS) and Bank Indonesia for the period from 1994 to 2023. The results show that monetary policy has a significant impact on the export of Indonesia’s fisheries products. Specifically, the real exchange rate has a significant negative effect on exports, where depreciation of the exchange rate reduces the competitiveness of Indonesian fisheries products. Interest rates have a significant positive effect, indicating that higher interest rates can stimulate exports through increased investment and competitiveness. Inflation also has a positive and significant effect, showing that controlled inflation can enhance foreign market purchasing power for Indonesian fisheries products. Simultaneously, the three variables real exchange rate, interest rates, and inflation have a significant impact on the export performance of Indonesia’s fisheries subsector. Overall, stable monetary policies, particularly in managing exchange rates, interest rates, and inflation, can improve the export performance of Indonesia’s fisheries subsector. This study suggests that the Indonesian government should pay more attention to the impact of monetary policy on exports to enhance competitiveness in global markets.